"Bukreev (left), trade union organiser, receives a contribution from the Stakhanovite Novikov, to help the Spanish republican fighters." Further information on back. Copied from collection CNT - Trojanovskij, ...,
"Bukreev (left), trade union organiser, receives a contribution from the Stakhanovite Novikov, to help the Spanish republican fighters." Further information on back. Copied from collection CNT.